Determination of the Active Chemical Compounds and the Antibacterial Activity of Various Fractions of Lawsonia inermis L. - Sri Mulyaningsih; Febriyati Adji Rachmadani (Borneo Journal of Pharmacy, 2022)
Lawsonia inermis L., or henna leaves, are usually used to treat wounds on the skin. Lawsonia inermis contain naphthoquinones, flavonoids, tannins, and saponins. The antibacterial activity of L. inermis leaf extract in various solvents has been extensively studied. However, which component is responsible for the antibacterial activity is still unknown. This study was intended to investigate the antibacterial effect of L. inermis fractions against Staphylococcus aureus and to discover the antibacterial chemical class in the most active fraction. The methanol extract was fractionated with n-hexane and ethyl acetate subsequently. The antibacterial activity of various fractions was tested using the well diffusion method. TLC-bioautography was used to identify the class of active chemicals as antibacterial agents. Antibacterial activity against S. aureus was highest in the ethyl acetate fraction. TLC-bioautography of the ethyl acetate fraction showed inhibition areas at Rf values of 0.25 and 0.53, respectively, indicating the naphthoquinones and phenolic compounds groups. In conclusion, naphthoquinones and phenolic compounds are suggested to contribute to the antibacterial effect of the ethyl acetate fraction of L. inermis leaves.